IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT (TQM) IN RAISING THE QUALITY OF EDUCATION IN PRIVATE MADRASAH TSANAWIYAH - Ahmad SETIAWAN (Journal of Education and Leadership in Education, 2019)
This research in purposes is to implement the Total Quality Management (TQM) to raise the Quality of education in private Madarasah Tsanawiyah (MTs. Muhammadiyah Bandung. The research method used is qualitative method. The sampling technique is purposive sampling. Data will use primer data, which taken directly from the respondent and secondary data which become supporting data. Based on the research result, the Implemetation of Total Quality Mangement of privat Madrasah Tsanawiyah is very good. By good steps and commitment effort and also focus in realizing the vision, mission, and purposes of the school applying school’s program strategicly and continuously.Explorating the potential of human and natural resources and developing relationship with harmony between schools and the stakeholders and also processing creativity and innovation program of the school. Every obstacle and innovation became the first step to motivate the school to optimize the potentials so we can act that every weak and obstacle is never exist.